Development and bicultural validation of the New Sexual Satisfaction Scale - Štulhofer, Aleksandar (Array, 2010)
The development and bi-cultural validation of the New Sexual Satisfaction Scale (NSSS), a 20 item multi-dimensional composite measure of sexual satisfaction is presented. The development of the scale was based on a 5-dimension conceptual model that emphasized the importance of multiple domains of sexual behavior including sexual sensations, sexual awareness/focus, sexual exchange, emotional closeness, and sexual activity. Scale construction and validation were carried out using seven independent samples with over 2000 participants aged 18-55 in Croatia and the United States (U.S.). Primary data collection was completed using online survey tools. While analyses did not confirm the proposed conceptual structure, they did support a two-dimensional factor structure focusing on self (“ ego-centered” ) and other (“ partner and sexual activity centered” factor) domains, each of which contained items representing all five conceptual dimensions. Scale reliability (k=20) was satisfactory for all samples and construct validity was confirmed in both cultures. The NSSS was also found to have acceptable one-month stability. It is suggested that the NSSS may be a useful tool for assessing sexual satisfaction regardless of person’ s gender, sexual orientation, and relationship status.